If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+66=x+86+50
We move all terms to the left:
x+66-(x+86+50)=0
We add all the numbers together, and all the variables
x-(x+136)+66=0
We get rid of parentheses
x-x-136+66=0
We add all the numbers together, and all the variables
-70!=0
There is no solution for this equation
| -13=8x+5-2x | | (X+3)(x×4)=(x+1)(x+2) | | 6x+9=6x-1 | | =k−22 | | -2-7x+x=-14 | | -9+3x+4=12 | | 356=k−22 | | r+833=865 | | 8+5n+n=-10 | | 598=26k | | 2m+1/5=3m-4/6 | | 0=3x^2-20x-30 | | |x-6|=49 | | 5/6m=3/6 | | -3(y+30)=2y+3 | | 4n/n+3=5/2 | | -8x^-3+2x^-2=0 | | 6=-2-5^2a | | 30=x(3x-20) | | 42/n+3=5/2 | | -6x+4-2x=-4 | | -2k+12=-4k-2 | | b=4(22) | | 46=3x+9 | | 2/3x+4=-1/3x-4 | | 7+4x=1-8x+1-7 | | 4y-4*8=9y+5*8-117 | | -7(b+3)=-1/2(5b-9) | | 90=55(x-25) | | 2x=+73(2-x) | | -2y-9y=0 | | 9w=2970w |